APLIKASI MEDIA PEMBELAJARAN FISIKA BERBASIS SPARKOL VIDEOSCRIBE PADA POKOK BAHASAN SUHU DAN KALOR TERHADAP HASIL BELAJAR SISWA SMK - Miftachul Jannah; Alex Harijanto; Yushardi Yushardi (JURNAL PEMBELAJARAN FISIKA, 2019)
Physics was considered a difficult subject and less attractive to students. Students tend to be less active in the learning process in classroom, so the values obtained are relatively low. This is influenced by several factors, one of which is the learning media used by teacher in delivering less innovative material. Therefore, there is a need for creative and innovative learning media. Through Sparkol VideoScribe learning media the subject matter is explained images, animations and sounds which are systematically presented in compact videos, so that they are expected to improve student learning outcomes. This type of research was experimental with Pretest-Posttest Control Group Design. The subjects research is one of the Vocational Schools in Jember. Data acquisition techniques through test, observation, interview and documentation. The data analysis technique used Independent Sample T-Test with SPSS 23 and student response questionnaire sheets. Based on results and discussion the conclusions are as follows: 1) There is a significant influence Sparkol VideoScribe based physics learning media on student learning outcomes; 2) Sparkol VideoScribe based physics learning media effectively used in learning process and 3) students' responses to Sparkol VideoScribe based physics learning media can be categorized as positive or well used in classroom learning.Keywords : Physics Learning, Sparkol VideoScribe, effectively, students respon